Penerapan Metode Discovery Learning untuk Meningkatkan Aktivitas Hasil Belajar Al-Qur’an dan Hadits Pada Materi Keotentikan Al-Quran - Rosmawar, Rosmawar; Zulfadhli, Zulfadhli (Jurnal Nispatti, 2024)
The aim of this classroom action research is to improve the activities and learning outcomes of Al-Quran Hadith on the Authenticity of the Al-Quran material through the application of the Discovery Learning model. This research was carried out at MAN 2 Aceh Besar. The research was carried out for 3 months, from February to April 2019. The data source came from class X-IPS 2 students in the odd semester of the 2018/2019 academic year. The number of students is 18 students with 11 male students and 7 female students. Data collection tools include test items and student activity instrument sheets. Data validation is carried out by entering student test scores into a previously prepared score list and data validation for the observation sheet is carried out by checking the prepared observation sheet. The research procedure consists of two cycles. Each cycle consists of planning, implementation, observation and reflection. The pre-cycle research results were 44.4% with an average value of 69.7, while in Cycle I it was 66.7% with an average value of 75 and while in Cycle II the percentage of completion reached 100% with an average value of 79.7. The gradual implementation of Discovery Learning has been able to increase student learning activities, so that it has a very significant impact on improving student learning outcomes.